IoT Based Vehicle Emission Monitoring and Alerting System - Devan, P.A.M. (Institute of Electrical and Electronics Engineers Inc., 2019)
This study was carried out to analyze the variations of hazardous pollutants like Carbon Monoxide (CO), Carbon Oxides (COx) and Nitrogen Oxides (NOx) in Tamil Nadu. The major source of air pollution in urban areas mainly in developing countries like India is due to the transportation sector. Road and Transportation Office (RTO) and Central Pollution Control Board (CPCB) are the monitoring authorities of the emission standards. This paper measures the emissions standards in a real-time process using various sensors namely smoke sensor which is placed at the exhaust of the vehicle. The data collected verifies the standard limits and provides information to the vehicle operator, RTO, and CPCB through the Global System for Mobile Communication (GSM) and the Internet of Things (IoT) for further analysis. The Indian government provides the Fitness Certificate (FC) for every vehicle by monitoring its behaviour. The control strategy coding for calculating the emitted gas limits has been done in PIC Microcontroller which analyzes the data and yields the statistics which are then compared with the standard values. Drivers and nearby control stations are provided with continuous feedback and warnings if the limits are exceeded. The Gas sensor is installed in the proposed control system by indicating the values provided in the Liquid Crystal Display (LCD). Â© 2019 IEEE.